Threats and opportunities for European pharmaceutical wholesalers in a changing healthcare environment - Cmolik, Andreas (Diplomica Verlag, 2012)
HauptbeschreibungThe aim of this book is to identify the major drivers of change within the European healthcare systems and to evaluate risks and opportunities confronting pharmaceutical full-line wholesalers. These businesses are the most important link between pharmaceutical manufacturing and the point of sale; providing one-stop-shopping for healthcare professionals across Europe. While on the one hand European governments are interested to ensure broad access to healthcare provision for the general public with a high level of quality, they are on the other hand concerned with limiting cost.